2014
DOI: 10.1515/revic-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic water splitting – from coordination chemistry to catalysis

Abstract: AbstractThis review gives an overview on the recent developments in the field of coordination chemistry of water at transition metal centres, which could give implications for a better understanding of the elementary steps of light-driven overall water splitting. Additionally, selected examples for homogeneous catalyst systems that are capable of producing hydrogen and/or oxygen from water are presented, focussing on the mechanistic aspects of water reduction and water oxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Some of the carbon is sequestered by the manganese in the form of Mn II (bi)carbonate salts as indicated from the EPR and ATR-FTIR characterization of the precipitates. However, if water is excluded, a different "anhydrous" precipitate forms (2). The rapidity at which 2 decomposes in air has complicated its identification and is an ongoing effort in our laboratory.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the carbon is sequestered by the manganese in the form of Mn II (bi)carbonate salts as indicated from the EPR and ATR-FTIR characterization of the precipitates. However, if water is excluded, a different "anhydrous" precipitate forms (2). The rapidity at which 2 decomposes in air has complicated its identification and is an ongoing effort in our laboratory.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It follows that efforts in solar energy storage by means of water-splitting technology could benefit from the strategic application of organometallic catalysts. 1,2 In particular, a small class of organometallic chromophores that contain water-derived ligands mediate light-driven water-splitting transformations producing both a reduced and oxidized water-derived product. Milstein and coworkers discovered one of the first of these water-splitting systems using light and a ruthenium pincer pyridine complex.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Currently, besides direct electrolysis, [9][10][11][12][13][14][15] artificial water reduction strategies usually require a reduced form of (s-or d-block) metal as a reactant or catalyst, where heterolytic O-H bond cleavage during the water splitting occurs through oxidative addition over one or two metal centres (Chart 1A). [16][17][18] The electron-rich metal centre accepts electrons from the electronegative oxygen and transfers it to a proton (in H 2 O) to form a hydride, which then recombines with the second proton on oxygen to generate dihydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…The scalable production of dihydrogen (H 2 ) from water and sunlight is a worthy pursuit for the purpose of clean energy. An interesting strategy, if at least to gain fundamental knowledge about chemical reactivity, is one that uses single-site molecular compounds for direct solar photoconversion of water into fuel. , While not yet practical, it is reported that certain molecular organometallic complexes split water (H 2 O) through reduction and oxidation reactions, producing H 2 and hydrogen peroxide (H 2 O 2 ) as the initial products. Analogous photochemical HY splitting (Y = halogen) and catalytic photochemical alkane dehydrogenation provide insight into the elementary reactions that might be involved in photochemical water splitting mediated by similar complexes. However, water has unique coordination chemistry and thus deserves special attention.…”
Section: Introductionmentioning
confidence: 99%